FOUR SENSOR GAS MICROSYSTEM BASED ON POROUS ANODIC ALUMINA SUBSTRATE: DESIGN, FABRICATION TECHNIQUE, SIMULATION - O. G. Reutskaya; Ya. A. Belahurau; I. A. Taratyn; V. V. Khatko (Приборы и методы измерений)
Design and fabrication technique of four sensor gas microsystem based on nanoporous anodic alumina have been developed. Simulation of basic elements′ temperature and thermo-mechanical deformation created in the microsystem construction has been carried out by finite element method. r-spacing:-.05pt'>боты микросистемы.